2014
DOI: 10.3389/fonc.2014.00114
|View full text |Cite
|
Sign up to set email alerts
|

Glycobiology of Neuroblastoma: Impact on Tumor Behavior, Prognosis, and Therapeutic Strategies

Abstract: Neuroblastoma (NB), accounting for 10% of childhood cancers, exhibits aberrant cell-surface glycosylation patterns. There is evidence that changes in glycolipids and protein glycosylation pathways are associated to NB biological behavior. Polysialic acid (PSA) interferes with cellular adhesion, and correlates with NB progression and poor prognosis, as well as the expression of sialyltransferase STX, the key enzyme responsible for PSA synthesis. Galectin-1 and gangliosides, overexpressed and actively shedded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 173 publications
(188 reference statements)
0
34
0
1
Order By: Relevance
“…Additionally, these molecules are also involved in various biological pathways that are implicated in pathogenesis and progression of tumors (Ahmed & Cheung, ). GD2 has a high expression on the surface of tumor cells originating from neuroectoderm, such as NB and melanoma, while has limited expression on normal tissues, principally in the cerebellum and peripheral nerves (Ahmed & Cheung, ; Berois & Osinaga, ; Saito et al, ; Suzuki & Cheung, ). Several reports revealed that GD2 contribute to the attachment of NB cells to the extracellular matrix (Ahmed & Cheung, ; Cheung et al, ; Kushner, Kramer, Modak, & Cheung, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these molecules are also involved in various biological pathways that are implicated in pathogenesis and progression of tumors (Ahmed & Cheung, ). GD2 has a high expression on the surface of tumor cells originating from neuroectoderm, such as NB and melanoma, while has limited expression on normal tissues, principally in the cerebellum and peripheral nerves (Ahmed & Cheung, ; Berois & Osinaga, ; Saito et al, ; Suzuki & Cheung, ). Several reports revealed that GD2 contribute to the attachment of NB cells to the extracellular matrix (Ahmed & Cheung, ; Cheung et al, ; Kushner, Kramer, Modak, & Cheung, ).…”
Section: Introductionmentioning
confidence: 99%
“…Galectin‐1 is involved in the regulation of cell growth, adhesion, signalling, differentiation and development, as well as immune system and host–pathogen interactions . Galectin‐1 plays an important role in sensory neuron development and synaptic connection in the embryonic spinal cord, and is overexpressed in various stages of cancer, with its role in cancer progression and metastasis being intensively reviewed . To date, several different types of synthetic glycoconjugates have been reported against galectin‐1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, within this positive population there remains heterogeneous expression of GD2 (Figure B). Clinically, the majority of neuroblastoma tumor cells exhibit GD2 on the cell membrane making it a prominent therapeutic target . Furthermore, high expression of GD2 is one of the hall marks of high‐risk neuroblastoma .…”
Section: Discussionmentioning
confidence: 99%